PREVALENCE AND CHARACTERISTICS OF INFERTILITY IN YOUNG WOMEN OF REPRODUCTIVE AGE LIVING IN ZABAYKALSKY DISTRICT - N. I. Frolova; T. E. Belokrinitskaya; L. I. Anokhova; N. V. Kadalova; O. V. Lugovskaya; Y. V. Yakimova; D. A. Ananjina; O. V. Turanova (Acta Biomedica Scientifica, 2014)
We conducted epidemiological research of WHO record for the estimation of prevalence and characteristics of infertility in young women living in Zabaykalsky District. The research included 2932 women of 18-35 years, 731 of them had infertility. Frequency of infertility exceeds 15% critical level, determined by WHO, and reaches 24,9 % (22,3 % - in town, 25,8 % - in countryside). Secondary infertility appears more often that primary one (54,2 % vs 45,8 %). 44,0 % of young infertile women don't plan pregnancy.